Neuro-immune Interactions in Metabolic Regulation: Brain and Adipose Tissue Crosstalk - Chan Hee Lee (Journal of Obesity & Metabolic Syndrome)
The global obesity epidemic underscores the urgent need to elucidate the mechanisms underlying metabolic disorders. Although excessive caloric intake and sedentary lifestyles have traditionally been viewed as primary contributors, recent evidence highlights significant roles for genetic, environmental, and immunological factors. Notably, dysfunction within the central nervous system (CNS), particularly the hypothalamus, has emerged as a crucial regulator of metabolic homeostasis through CNS-peripheral interactions. Hypothalamic inflammation is primarily mediated by microgliosis, which disrupts systemic homeostasis. This review discusses the detrimental effects of hypothalamic microgliosis on energy metabolism and highlights emerging evidence suggesting paradoxically beneficial roles of hypothalamic microgliosis in metabolic regulation. Within adipose tissue, immune cells, including adipose tissue macrophages (ATMs), T cells, and B cells, exert significant influence over systemic metabolism. Short-term activation of the sympathetic nervous system (SNS) promotes the anti-inflammatory polarization of ATMs and enhances the induction of regulatory T cells; thereby, improving insulin sensitivity. In contrast, chronic SNS activation may exacerbate inflammation due to β-adrenergic receptor desensitization and catecholamine resistance. Parasympathetic acetylcholine signaling is also known to suppress inflammation through activation of α7 nicotinic receptors on macrophages; however, parasympathetic innervation within white adipose tissue is considerably limited. Despite the critical role of the nervous system in systemic metabolism, comprehensive insight into neuro-immune interactions remains lacking. In-depth studies using advanced technologies are needed to deepen knowledge in this field and to cover novel therapeutic targets for obesity and related metabolic disorders.